2015
DOI: 10.1016/j.najef.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal causality between house prices and output in the US: A bootstrap rolling-window approach

Abstract: This paper examines the causal relationships between the real house price index and real GDP per capita in the U.S., using the bootstrap Granger (temporal) non-causality test and a fixed-size rolling-window estimation approach. We use quarterly time-series data on the real house price index and real GDP per capita, covering the period 1963:Q1 to 2012:Q2. The full-sample bootstrap non-Granger causality test result suggests the existence of a unidirectional causality running from the real house price index to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 51 publications
2
60
0
1
Order By: Relevance
“…The results imply that, along with the increase in the house prices, there is a significant decrease in the stock prices; therefore, the desirable policy instruments are required to evaluate the impact of house prices on the stock market in a given countries contexts. The results are consistent with previous studies of Batayneh and Al-Malki (2015) and Nyakabawo et al (2015), both these studies confirmed the negative relationship between stock prices and house prices across their countries. The short-and long-run causality results are shown in Table 4.…”
Section: Data Analysis and Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results imply that, along with the increase in the house prices, there is a significant decrease in the stock prices; therefore, the desirable policy instruments are required to evaluate the impact of house prices on the stock market in a given countries contexts. The results are consistent with previous studies of Batayneh and Al-Malki (2015) and Nyakabawo et al (2015), both these studies confirmed the negative relationship between stock prices and house prices across their countries. The short-and long-run causality results are shown in Table 4.…”
Section: Data Analysis and Resultssupporting
confidence: 92%
“…Batayneh and Al-Malki (2015) concluded that house prices have a significant and positive association with the stock prices in Saudi Arabia financial markets that escalate a country's economic growth; on the other hand, the study established the stock led house prices in a country. Nyakabawo, Miller, Balcilar, Das, and Gupta (2015) supported the house prices led the economic growth hypothesis by using the consistent time series quarterly data of the US, which shows the soundness of the financial market to support the economic system in a country. The study formulated the third hypothesis regarding the causal relationship between stock prices and house prices, i.e.,…”
Section: H2: House Prices and Stock Prices Both Are Co-integrated In mentioning
confidence: 72%
“…Accordingly, higher income increases housing demand which raises the real estate prices. These inter-linkages are generally formalized in the housing literature by assuming a stable long-run relationship between house prices and economic fundamentals (Abraham and Hendershott, 1996;Meen, 2002;Capozza et al, 2002;Nyakabawo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These include Jud and Winkler (2002), Hwang andQuigley (2006), Gallin (2006), Demary (2010), Miller et al (2011) and Nyakabawo et al (2013). Jud and Winkler (2002) and Hwang and Quigley (2006) study the dynamics of metropolitan housing prices and find that real house price appreciation is strongly driven by fundamentals including income.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation